Dampak Covid-19 Terhadap Jumlah Pengunjung The Harber Café dan Resto Politeknik Harapan Bersama Tegal - Puput Dewi Anggraeni; Dina Hariani (Politeknik Harapan Bersama, 2022)
Covid-19 has an impact on all sectors, including the tourism sector. The impact of covid-19 is also very influential on culinary businesses or restaurants, because of the limited open schedule and for customers who come or dining are also very limited, this makes most customers prefer to buy food through online applications or make their own dishes at home. It is more healthier and hygienic. Therefore, many culinary businesses suffered losses and went out of business. As happened at The Harber Café and Resto Polytechnic Harapan Bersama, since the covid-19 pandemic, daily income has decreased very drastically, resulting in very large losses from April 2020 until now. This happened for the first time when the Tegal City government imposed the first large-scale social restrictions (PSBB) on April 23, 2020. The methods used included data collection and data analysis using qualitative descriptive analysis. The results of this study are that the COVID-19 pandemic has had a major impact on visitors to The Harber Café and Resto at the Harapan Bersama Polytechnic, with a significant decrease in cafe income and the number of cafe visitors as well as a decrease in cafe employee salaries.